Influence of tendon injuries on the clinical outcome of ankle and hindfoot fractures. Issue 3 (April 2022) - Cardoso, Afonso; Mira, Catarina; Ataíde, Mónica; Protásio, João; Vide, João; Resende Sousa, Manuel; Mendes, Daniel
Abstract: Background: Associations of tendon injuries with ankle and hindfoot fractures is a current concern and recent research has linked specific fractures with specific tendon injuries, despite its functional impact being unknown. The purpose of this study is to assess that impact. Methods: Computed tomography scans of patients with ankle and hindfoot fractures were reviewed for tendon injuries. Patients were clinically evaluated with the Visual Analogue Scale (VAS) and the Manchester–Oxford Foot Questionnaire (MOXFQ), via a telephonic interview. Results: Eighty-five patients were included in the study. The mean age was of 49.9 ± 16.5 (14–80) years and there were 43 females (50, 6%). Mean follow-up was of 43, 7 ± 15, 1 (24, 4–82, 2) months. Tendon injuries were identified in 23 patients (27, 1%) and the most common lesion was tendon entrapment. The tibialis posterior tendon (TP) was injured in 18 patients (21, 2%) and comprised 58, 1% of all tendon injuries. Tendon injuries were mostly associated with pilon fractures, which was the most common fracture type (44, 7%). There was no clinical difference between patients with a tendon injury [VAS of 4, 3 ± 2, 6 (0–8) and MOXFQ score of 35, 1 ± 22, 4 (5–80)], and those without [VAS of 3, 9 ± 2, 5 (0–10) and MOXFQ of 34, 3 ± 26, 0 (0–95), respectively (p = 0, 281 and 0, 689)]. Conclusion: Tendon injuries were present in 27% of patients with ankle and hindfoot injuries. The most frequently injured tendon was the TP in association with pilon fractures, with entrapment being the most common lesion. These lesions, however, do not seem to reflect in a worse functional outcome at two years of follow-up.